Islamic Reformism in a Comparative Perspective: A Study of the Thought of Jamaluddin al-Afghani and Muhammad Abduh and Their Relevance to Contemporary Muslim Society - Irfan Padlian Syah; Sholahuddin Al Ayubi; Andi Rosa (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This article presents a comparative study of the Islamic reformist thought of Jamaluddin al-Afghani and Muhammad Abduh as responses to European colonialism and the epistemological crisis facing the Muslim world in the nineteenth century. Although both figures are often treated as representatives of a homogeneous intellectual tradition, this study reveals fundamental divergences in their epistemological foundations, reform agendas, and methods of change. Employing a qualitative library research approach with historical, analytical, and comparative methods, this study finds that al-Afghani constructed a politically militant epistemology that positioned reason as an instrument of resistance against colonial hegemony, while Abduh developed a more systematic theological rationalism emphasizing the harmonization of reason and revelation. Regarding their reform agendas, both agreed that Islamic revival does not entail Westernization, yet differed in their priorities: al-Afghani privileged top-down political transformation, whereas Abduh prioritized bottom-up educational and institutional reform. The study concludes that these two approaches are complementary rather than contradictory, and that both remain highly relevant for contemporary Muslim societies, particularly Indonesia, in addressing the challenges of radicalism, intolerance, and modernization.